New Paradigm of Contemporary Hermeneutics: Analysis of Religious Text Discourse Understanding of Paul Ricoeur’s Perspective - Ahmad Atabik (LPPM IAIN Kudus, 2019)
The hermeneutic study about discourse before the existence of Paul Ricoeur was around three points: romantic hermeneutics, onology hermeneutics, and dialectical hermeneutics. They have characteristics that other mainsteams do not have. Ricoeur’s thought style cannot be included in any of those three hermeneutic thoughts. In fact, his thought covers almost all contemporary philosophical topics. One of the points of Ricoeur’s contemporary hermeneutics is how to combine the phenomenology of Husserl’s metaphysical tendencies with Heidegger’s existential phenomenology. The text is essentially autonomous to carry out “de-contextualization” (the process of liberating oneself from context) and “re-contextualization” (the process of returning to context). Ricoeur’s thought patterns cannot be included in one of the three hermeneutic thought. In fact, his thought allegedly covers almost all contemporary philosophical topics. One of Ricoeur’s contemporary hermeneutics is how to combine the phenomenology of Husserl’s metaphysical tendencies with Heidegger’s existential phenomenology.